2005
DOI: 10.1007/s11094-005-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of 2,4-Dibenzyloxy(Diallyloxy)carbonyl-3-aryl-5-hydroxy-5-methylcyclohexanones

Abstract: A series of 2,4-dibenzyloxy(diallyloxy)carbonyl-3-aryl-5-hydroxy-5-methylcyclohexanones have been obtained via reactions of benzylacetoacetate and allylacetoacetate with aromatic aldehydes in the presence of a basic catalyst (piperidine). The proposed structures are confirmed by the results of 1 H NMR spectroscopy, IR absorption spectroscopy, and high-resolution mass spectrometry measurements. Data on the antimicrobial activity of the synthesized compounds are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The results showed that the studied compounds (Table 3) possess weak antimicrobial activity, in contrast with previously synthesized dialkyl-2-aryl-6-hydroxy-6-methyl-4oxocyclohexane-1,3-dicarboxylates [1,2].…”
Section: Experimental Biological Partmentioning
confidence: 68%
See 1 more Smart Citation
“…The results showed that the studied compounds (Table 3) possess weak antimicrobial activity, in contrast with previously synthesized dialkyl-2-aryl-6-hydroxy-6-methyl-4oxocyclohexane-1,3-dicarboxylates [1,2].…”
Section: Experimental Biological Partmentioning
confidence: 68%
“…It was established earlier that the reaction of esters of acetoacetic acid with aromatic aldehydes in the presence of a basic catalyst forms dialkyl-2-aryl-6-hydroxy-6-methyl-4oxocyclohexane-1,3-dicarboxylates (b-cycloketoles), some of which exhibit antimicrobial activity [1,2].…”
mentioning
confidence: 99%
“…The antimicrobial activity of the synthesized compounds has been evaluated.It was established previously that b-cycloketols and their derivatives exhibit antimicrobial and anti-inflammatory activity [1,2]. It seemed interesting to study the reaction of dialkyl 2-aryl-6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates with tosylhydrazine in order to synthesize new biologically active compounds.…”
mentioning
confidence: 99%